Kuat Tekan Mortar Geopolimer Pofa Yang Dirawat Pada Suhu Ruang - Lora Mona Tambunan; Monita Olivia; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research focus on study of palm oil fuel ash based geopolymer mortar which use room temperature curing condition. Amount of Portland Cement (OPC) was added to accelerate setting time of geopolymer paste. The main ingredient to make geopolymer mix use palm oil fuel ash (POFA) which contain Silica (Si) and Alumina (Al) from Dumai, Riau province activated by alkaline activator solution. Alkaline activator solution was combined by NaOH 16M and liquid of natrium silikat (Na2SiO3 ) with SiO2 to Na2O mass ratio 2,3. Alkaline activator content as 100% of total binder. Rest period of geopolymer mortar for 5 days. The geopolymer paste was cast in cube mould 50x50x50 mm. The research show the compressive strength of geopolymer mortar which addition OPC variation. This study aims that compressive strength were improved simultanesly mount of addition OPC. Keywords: geopolymer, palm oil fuel ash, room temperature, addition OPC